The future of EU blended finance and guarantees: An assessment of cooperation strategies with least developed countries in Africa - Erik Lundsgaarde (German Institute of Development and Sustainability (IDOS), 2023)
The European Fund for Sustainable Development Plus (EFSD+) is a core element of EU development cooperation and reflects the EU's strong commitment to deploying blended finance and guarantees as development financing tools. This discussion paper examines the EU's intentions concerning how the EFSD+ will be integrated into geographic programmes, focussing on the least developed countries (LDCs) in Africa. Based on a review of the Multiannual Indicative Programmes (MIPs) for 30 African LDCs as well as the regional MIP for Sub-Saharan Africa covering the period 2021-2027, the paper provides an overview of funding reserved for EFSD+ implementation in geographic programmes, identifies the expected EFSD+ sectoral priorities and summarises references to development finance institutions (DFIs) as EFSD+ implementation partners. This descriptive review highlights issues for the future monitoring and assessment of the EFSD+. The paper points to uncertainty about the magnitude of the management challenge that EU institutions face in EFSD+ implementation given the difficulties of predicting the scale of guarantee-backed operations in individual countries, the lack of information on the expected volume of blended finance operations, and the limited analysis of how EFSD+ tools relate to other EU funding approaches. The paper also notes that EU institutions should be more explicit about the criteria shaping EFSD+ resource commitments to clarify relevant prerequisites for the effective deployment of EFSD+ tools. Finally, the broad thematic scope for EFSD+ use implies that knowledge about how blended finance and guarantees function and how the financing approaches interact with other interventions needs to increase throughout the EU system.
Keywords: 330; Africa; European development policy; development financing